2014
DOI: 10.3329/jom.v15i1.19881
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Polychondritis: Case Report and Review of the Literature

Abstract: Relapsing polychondritis is a rare, severe, episodic and progressive inflammatory disorder of unknown aetiology and autoimmune pathogenesis, causing recurrent inflammation of involving cartilaginous structures, predominantly those of the ears, nose, and laryngotracheobronchial tree. Rarity of this disease, array of many possible presenting symptoms, lack of specific diagnostic investigation and episodic nature often causes significant delay in diagnosis. We are reporting a 55 year old woman presenting with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…3 Recently Haque MA et al reported a case of RP from Bangladesh. 10 But our patient was unique in that he had associated neurological features and MDS.…”
Section: Case Reportmentioning
confidence: 99%
“…3 Recently Haque MA et al reported a case of RP from Bangladesh. 10 But our patient was unique in that he had associated neurological features and MDS.…”
Section: Case Reportmentioning
confidence: 99%